EMPLOYEE PERFORMANCE ANALYSIS BASED ON EDUCATION AND WORK DISCIPLINE IN THE COOPERATIVES AND MICRO, SMALL & MEDIUM ENTERPRISES (MSMEs) DEPARTMENT OF MALANG REGENCY - Yusuf Iskandar (International Journal of Economics and Management Research, 2022)
Education can be defined an activity that is carried out in school. Work discipline means an attitude to respect and obey the applicable rules, both written and unwritten, as well as able to follow the rules and to be given sanction for every violation to the duties and authorities given. This research aimed to: 1) analyze the effect of education on employee performance; 2) analyze the effect of discipline on employee performance; 3) analyze the effect of education and work discipline on employee performance in Cooperatives and Micro, Small & Medium Enterprises (MSMEs) Department of Malang Regency. This research method used quantitative methods with primary and secondary data. The data were collected through library study and field study with a sample of 65 people. The data analysis used multiple linear regression assisted by SPSS version 24. The results shows that education has no significant effect on employee performance. In contrast, work discipline has a significant effect on employee performance. Both education and work discipline do not significantly affect employee performance in the Cooperatives and Micro, Small & Medium Enterprises (MSMEs) Department of Malang Regency.